1996
DOI: 10.1080/07315724.1996.10718561
|View full text |Cite
|
Sign up to set email alerts
|

Association of macronutrients and energy intake with hypertension.

Abstract: Hypertension, a major public health problem, becomes more prevalent during aging. Epidemiological studies suggest that environmental factors such as nutrition may play a major role in blood pressure (BP) regulation. It is generally accepted that obesity and sodium/alcohol consumption are important factors, and many believe that calcium, magnesium and potassium consumption are regulatory as well. Less emphasis has been placed on whether macronutrients influence blood pressure significantly. This review focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 3 publications
0
8
0
2
Order By: Relevance
“…Co., Korea). The liver TC and TG were assayed by the same method as described for the plasma TC and TG after the treatment with Triton X-100 (Preuss et al, 1996). …”
Section: Methodsmentioning
confidence: 99%
“…Co., Korea). The liver TC and TG were assayed by the same method as described for the plasma TC and TG after the treatment with Triton X-100 (Preuss et al, 1996). …”
Section: Methodsmentioning
confidence: 99%
“…The interplay between nutritional factors and hypertension has been discussed in many studies. 9 However; further question is worth to be asked whether there are other factors which are more prominent than nutritional factors in the elderly population, leading to the occurrence of hypertension. WHO Scientific Group reported that both nutritional and non nutritional factors such as physical activity, alcohol and stress can be additional risks to the occurrence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning gender, Jenner DA et al observed in 9 years old Australian children that SBP was negatively associated to calorie-adjusted protein intake in girls, while no detectable relationships between BP and calorie-adjusted intakes of fats, carbohydrates, sodium, potassium, calcium, magnesium was reported [100]. The possible effect of protein on BP could be explained by the vasodilating properties of certain amino acids, which determine an increased production of nitric oxide [101]. Fiber intake might also influence children’s BP [99,102].…”
Section: Introductionmentioning
confidence: 99%